Poems By the Way - Morris, William, 1834-1896 (Salt Lake City, UT : Project Gutenberg, 2002)
"Poems By the Way" by William Morris is a collection of poetry written in the late 19th century. The work reflects Morris's romantic sensibilities, encompassing themes of nature, love, and the interplay between reality and myth. It may appeal to readers who appreciate lyrical poetry that evokes strong emotions and vivid imagery. The opening of the volume introduces the poem "From the Upland to the Sea," where the speaker expresses a longing for a shared moment with a beloved, wandering through nature as spring unfolds. The imagery captures the beauty of the changing seasons, highlighting the joy and melancholy intertwined with love. Following this, the excerpt transitions into "Of the Wooing of Hallbiorn the Strong," a narrative piece that tells the story of a character's pursuit of love against the backdrop of Icelandic lore. This mixture of personal reflection and storytelling sets a tone that invites readers to explore the broader explorations of human experience found throughout the collection. (This is an automatically generated summary.)
Release date is 2002-10-01
Transcribed from the 1896 Longmans, Green and Co. edition by David Price
Keywords: English poetry -- 19th century